The “Future Search Conference” on Personal Identities Basis of The District Health System Network in Uttaradit Province / การแสวงหาอนาคตร่วมกันบนพื้นฐานอัตลักษณ์ส่วนบุคคลของเครือข่ายสุขภาพระดับอำเภอในจังหวัดอุตรดิตถ์ - Supannee Kluanklad / มณฑิรา อินจ่าย ศุภสิทธิ์ ต๊ะนา และสุพรรณี เกลื่อนกลาด, Montira Injai, Supasit Tana and (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 1 (2558): January - April 2015, 2015)
การศึกษาครั้งนี้มีจุดมุ่งหมายเพื่อเสนอประสิทธิผลของการใช้เทคนิค “การประชุมเชิงปฏิบัติการเพื่อแสวงหาอนาคตร่วมกัน” ในการ ทำความเข้าใจสถานการณ์อดีตและปัจจุบันที่มีความเชื่อมโยงกัน ซึ่งจะมีผลต่ออนาคตของแผนการปฏิบัติงานสร้างเสริมสุขภาพในพื้นที่ 4 อำเภอของจังหวัดอุตรดิตถ์ คือ ตรอน ฟากท่า น้ำปาด และบ้านโคก กลุ่มตัวอย่าง จำนวน 43 คน ได้แก่ ผู้บริหาร ทีมงานสุขภาพระดับอำเภอ และผู้นำชุมชน ที่มีภูมิหลังทางประสบการณ์และตำแหน่งงานเหมาะสมกับวัตถุประสงค์ของการจัดประชุมซึ่งเป็นรูปแบบหนึ่งของ การวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมบนพื้นฐานของอัตลักษณ์ส่วนบุคคลที่เน้นการใช้แนวคิดผู้นำ 4 ทิศจากรูปแบบบุคลิกภาพแบบ DISC เพื่อให้ผู้เข้าร่วมโครงการวิจัยสามารถเข้าใจความแตกต่างระหว่างบุคคลที่จะร่วมเป็นเครือข่ายการปฏิบัติงานในอนาคต การแปลผลข้อมูล ใช้สถิติพรรณนาและการวิเคราะห์เนื้อหา ผลการวิจัย พบว่า การใช้เทคนิคการประชุมเชิงปฏิบัติการเพื่อแสวงหาอนาคตร่วมกัน โดยแบ่งเป็นกลุ่มผสมที่แยกตามอัตลักษณ์ และกลุ่มเฉพาะที่แยกตามพื้นที่ปฏิบัติการ ประสบความสำเร็จในการเอื้ออำนวยช่วยให้ผู้เข้าร่วมโครงการ เกิดความความเข้าใจสถานการณ์ในอดีตอย่างชัดเจน ไม่หมดหวังกับปัญหาปัจจุบัน และสามารถวางแผนมุ่งสู่อนาคตที่พัฒนาได้จริง ทั้งนี้ ประเด็นสำคัญที่ผู้เข้าร่วมโครงการเห็นพ้องกันว่ามีผลกระทบมากที่สุด คือ การบริหารจัดการ โดยเสนอแนวทางพัฒนาใน 3 ด้าน ได้แก่ 1) การมีเครือข่ายเข้มแข็งที่ประชาชนใส่ใจดูแลสุขภาพด้วยตนเองมากขึ้น 2) การระบุค่ากลางของฐานข้อมูลที่เกี่ยวข้องกับระบบสาธารณสุขในพื้นที่อำเภอ และ 3) การให้นายอำเภอเป็นประธานเครือข่ายอำเภอสร้างเสริมสุขภาพเพื่อความเป็นเอกภาพในการบริหารจัดการ   คำสำคัญ : การประชุมเชิงปฏิบัติการเพื่อแสวงหาอนาคตร่วมกัน  อัตลักษณ์  เครือข่ายสุขภาพระดับอำเภอ    The purpose of this study was to identify the effective strategic developments arising from the “Future Search Conference” (F.S.C.). The conference was held in order to understand the linkage of past and present situations which had effect on the future of health promotion of 4 districts in Uttaradit province which is Tron, Fak Tha, Nam Pat, and Ban Khok. The 43 participants were executives, district health teams, and community leaders with appropriate experience and professional background to contribute to the aims of the conference. The F.S.C. was one of participatory action research based on the personal identities which comprise the four direction leadership approach with the DISC model to enable the participants to understand individual differences for working together in the future. Data were interpreted by descriptive statistics and content analysis. The research results showed that dividing the participants into mixed groups by psychological identity and then regrouping into operational areas in the F.S.C process was an effective technique to facilitate the participants to understand the past situation more clearly, not to give up on the present problems,  and encourage each other to develop a realistic future plan. The participants stipulated that an administration issue was the most important common idea for future strategic developments, which were: 1) strengthen the district health system network in order to empower people with more self-care; 2) specify the central value of the district health database; and 3) delegating the district chief officer as the chairman of the district health system network for the unity of management.        Keywords: Future Search Conference, Identity, District Health System Network
Keywords: การประชุมเชิงปฏิบัติการเพื่อแสวงหาอนาคตร่วมกัน อัตลักษณ์ เครือข่ายสุขภาพระดับอำเภอ Future Search Conference, Identity, District Health System Network